Effects of pepsin A on heat shock protein 70 response in laryngopharyngeal reflux patients with chronic rhinosinusitis. (2nd December 2017) - Wang, Jing; Yu, Zhao; Ren, Jianjun; Xu, Yang; Zhang, Yuke; Lei, Lei; Zheng, Yongbo; Huang, Ligao; He, Zhaoping
Abstract: Objectives: We investigated the relationship between laryngopharyngeal reflux (LPR) and chronic rhinosinusitis (CRS), and explored the effects of pepsin A on the level of heat shock protein 70 (HSP70) in CRS. Methods: We included 23 CRS patients with nasal polyps (CRSwNP), 26 CRS patients without nasal polyps (CRSsNP) and nine normal controls to measure pepsin A levels in nasal secretions, blood plasma and nasal tissues, to measure HSP70 levels in nasal tissues, and to detect pepsinogen A, HSPA5, cyclo-oxygenase-2 (COX-2), and carbonic anhydrase III (CAIII) mRNA expression levels in nasal tissues. Results: Pepsin A levels in nasal secretions were significantly higher in CRSwNP/CRSsNP patients than in controls. HSP70 levels were significantly increased in pepsin A-positive turbinate mucosa compared to controls ( p < .001). Similarly, HSP70 levels were significantly increased in pepsin A-positive polyp tissues than in pepsin A-negative polyp tissues ( p = .016). Furthermore, no association was found between the presence of pepsin A and HSPA5, COX-2, and CAIII mRNA expression levels. Conclusions: These results suggest that LPR may play a role in the development of CRS through pepsin A reflux, and increased HSP70 expression may be associated with the pathogenic mechanism of mucosal injury in CRS.